On Measuring the Social Opportunity Cost of Labour in the Presence of Tariffs and an Informal Sector (The Distinguishedl Lecture) (The Pakistan Development Review, 1992)
Harberger introduced his influential 1971 essay with the following words. This paper is intended not as a scientific study, nor as a review of the literature, but rather as a tract - an open letter to the profession, as it were - pleading that three basic postulates be accepted as providing a conventional framework for applied welfare economics. The postulates are: (a) The competitive demand price for a given unit measures the value of that unit to the demander; (b) The competitive supply price for a given unit measures the value of that unit to the supplier; and (c) When evaluating the net benefits or costs of a given action (project, programme, or policy), the costs and benefits accruing to each member of the relevant group (e.g., a nation) should normally be added without regard to the individual(s) to whom they accrue.